2015
DOI: 10.1007/s40097-015-0154-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of nicotine sensor based on copper nanoparticles and carbon nanotubes

Abstract: An electrochemical sensor was prepared to detect nicotine by depositing copper nanoparticles (Cu NPs) on the surface of a glassy carbon electrode (GCE) modified with multi-walled carbon nanotubes (MWNTs). The modified electrode was characterized by scanning electron microscopy and cyclic voltammetry. The novel-modified sensor exhibited effective electrocatalytic activities toward anodic oxidation of nicotine. Calibration plot showed two linear regions with different sensitivity, 1.121 (r 2 = 0.982) in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Afterward, the application of the enzyme-linked immunosorbent assay (ELISA) based on hydroxyproline allowed for the verification of collagen proteins in the range of µg/mL [21,22]. Currently, electrochemical sensing platforms [23,24] that incorporate specific antibodies responsible for selective antigen detection are at the centre of research interest. These kinds of sensors are highly effective tools to recognise the target analyte, with significant sensitivity and selectivity [1,2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Afterward, the application of the enzyme-linked immunosorbent assay (ELISA) based on hydroxyproline allowed for the verification of collagen proteins in the range of µg/mL [21,22]. Currently, electrochemical sensing platforms [23,24] that incorporate specific antibodies responsible for selective antigen detection are at the centre of research interest. These kinds of sensors are highly effective tools to recognise the target analyte, with significant sensitivity and selectivity [1,2,25,26].…”
Section: Introductionmentioning
confidence: 99%
“…As per this method, 10 blank injections of 0.1 M NaOH were added and the DPV responses were recorded. LOD = 3 S B / S ( S B : standard deviation of 10 blank samples, S : slope of the calibration curve) [ 39 , 40 ]. The LOD of the electrochemical detection of EA in the rGO-Ag@SiO 2 –modified Au PCB was calculated to be 0.68 μM.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown [22] that B 12 N 12 is the most stable nanocluster among different X 12 Y 12 (X = Al or B and Y = N or P) cages. Nanostructured materials have been invoked more attention as chemical sensors due to high surface to volume ratio and high electronic sensitivity [23][24][25][26][27][28][29]. It has been previously demonstrated that the electronic properties of pristine BN nanotubes and graphene-like sheets are not sensitive toward presence of H 2 CO gas, and cannot be used as chemical sensors [29,30].…”
Section: Introductionmentioning
confidence: 99%